Ways to improve family-athlete-coach relations and their conflict triggers - Tashkinov, K. S.; Kim, T. K.; Kuzmenko, G. A. (Theory and Practice of Physical Culture, 2019)
For the last few years the ice hockey sport popularity has been on the rise in Russia. The study analyzes the barriers for constructive family-athlete-coach relations and ethical framework for the family-coach cooperation to facilitate the junior players` trainings. Experimental study was run in the Krylya Sovetov Ice Hockey Club to explore the potential conflict issues and facilitate the psychological and educational consulting service to the families to scale down tensions in the family-athlete-coach relationship. Our analysis of the family-family and family-coach conflict zones found the following basic conflict triggers: interfamily hostilities; family errors when selecting the individual coaches; and the family connections and influential contacts used for pressure on the coach. The conflicts were found mostly due to the `growing training workloads on the underage ice hockey player when his own responsibility is still underdeveloped and the coach is under permanent pressure from the family`. We developed an education psychology prioritizing model for families to scale down the potential conflict triggers based on correlations of the identified dependable causes and effects, with the potential conflicts of interests prevented by reasonable constructive businesslike communication to work out the best sport progress trajectories for the underage players.